The functional outcome of mini carpal tunnel release in Hospital Queen Elizabeth II - Anbarasan, Amaleswaran (2015)
Introduction Carpal tunnel syndrome (CTS) is a term which refers to any condition leading to compression of median nerve as it is transmitted in the carpal tunnel. The main complaints were paraesthesia and night pain. Clinical evaluations along with nerve conduction study are almost diagnostic of CTS. The treatment options for CTS can be classified into non operative and operative methods but patients treated surgically have better outcomes at one year than those treated nonoperatively. The outcome of carpal tunnel release (CTR) can be assessed either subjectively or objectively with each has its own advantages and disadvantages. This study assessed the functional outcome of vertical mini CTR at distal wrist crease. Objective The main objective of this study was to determine whether this particular method of mini CTR was safe, easily reproducible and qualitative assessment of the patients. The tools used to assess the functional outcome were the SYMPTOM SEVERITY SCALE (SSS) and FUNCTIONAL STATUS SCALE (FSS) questionnaire pre and post operatively at 3 months. Objectively, the hand grip strength was measured by using Jamar Hand Grip Dynamometer pre and post operatively at 3 months to gauge the outcome of carpal tunnel release. Methods 36 patients (40 hands) aged between 22 to 71 years of age who had been diagnosed to have CTS from nerve conduction studies were selected from Hospital Queen Elizabeth II and screened according to the pre-determined inclusion and exclusion criteria. On the day of surgery, written consents were taken and the patients pre operative SSS, FSS and hand grip strength were evaluated. Subsequently, the vertical mini incision CTR at distal wrist crease was performed by a single surgeon to avoid bias. 3 months after their surgery, patients were reassessed of the post operative SSS, FSS and hand grip strength. The patients were also asked pertaining return to work date, scar appearance and tenderness, complications and overall opinion and experience regarding the procedure. Results and conclusion The mean score for SSS reduced from 33.60 to 15.25 which signify that CTR was successful in reducing the patients’ symptoms. Likewise the mean score for FSS reduced from 26.65 to 11.25 post operatively which signify that the surgery was a success. The handgrip strength improved by 28 to 31 % on average 3 months after CTR. All the 36 patients who underwent the vertical mini carpal tunnel release at distal wrist crease were satisfied with the post operative scar which was barely visible. All but one lady developed Sudeck’s Dystrophy which later resolved. 3 hands had scar tenderness up to 3 weeks which resolved at 3 months. All patients except the lady who had Sudeck’s Dystrophy were able to return to work within 4 weeks from the date of surgery. Overall, all the 36 patients were able to return to good functional status after CTR at 3 months post operative.